2020
DOI: 10.3390/met10010106
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Welding of Thin Aluminum Plate onto Magnesium Alloy Plate Using a Gelatin Layer as a Pressure-Transmitting Medium

Abstract: Mg alloys are extensively used in various automotive, aerospace, and industrial applications. Their limited corrosion resistance can be enhanced by welding a thin Al plate onto the alloy surface. In this study, we perform the explosive welding of a thin Al plate, accelerated by the detonation of an explosive through a gelatin layer as a pressure-transmitting medium, onto two Mg alloy samples: Mg96Zn2Y2 alloy containing a long-period stacking ordered phase in an α-Mg matrix and commercial AZ31. The bonding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In addition, a small number of cracks were found at the end of the clad, which are perpendicular to the detonation direction, as shown in Figure 5a. This result is consistent with previous work, where the macromorphology of Mg/Al explosive welding plates was also studied [22]. These cracks might be caused by tensile waves.…”
Section: Characterization Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, a small number of cracks were found at the end of the clad, which are perpendicular to the detonation direction, as shown in Figure 5a. This result is consistent with previous work, where the macromorphology of Mg/Al explosive welding plates was also studied [22]. These cracks might be caused by tensile waves.…”
Section: Characterization Methodssupporting
confidence: 93%
“…Fronczek et al [20] prepared a three-layered A1050/AZ31/A1050 composite plate via explosive welding, where intermetallic phases of Mg 2 Al 3 and Mg 17 Al 12 were found in the local melting zone. Zhang et al [21] studied the effect of annealing on the interface microstructure and mechanical characteristics of AZ31B/AA6061 explosive welding plates and found that intermetallic compounds of Al 3 Mg 2 and Al 12 Mg 17 tended to be generated at the bonding interface when the annealing temperature was at and above 250 • C. Recently, Inao et al [22] explored a modified explosive welding technique to join a thin Al plate onto an AZ31 plate using a gelatin layer as the pressure-transmitting medium. However, all the reports referred to explosive welding of a thick Mg plate to a thick Al plate or a thick Mg plate to a thin Al plate.…”
Section: Introductionmentioning
confidence: 99%
“…Inao et al [5] joined a very thin aluminium plate to two different magnesium alloys (AZ31, Mg 96 Zn 2 Y 2 ) by explosion welding, using a gelatine layer as a pressure-transmitting medium. The lower energetic conditions associated with the use of a very thin flyer and the gelatine medium promoted better bonding quality than in conventional explosion welding.…”
Section: Contributionsmentioning
confidence: 99%
“…Similarly, many researchers have carried out welding of aluminum in combination with various materials, such as AA150/Mg‐AZ31B, [ 18 ] Al alloy/Stainless steel, [ 19 ] Al/Iron, [ 20 ] Cu/Al, [ 21 ] Al/Mg. [ 22–25 ]…”
Section: Introductionmentioning
confidence: 99%